2010
DOI: 10.1142/s179383091000067x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Group Testing and Learning Hidden Vertex Covers With Minimum Adaptivity

Abstract: Suppose that we are given a set of n elements d of which have a property called defective. A group test can check for any subset, called a pool, whether it contains a defective. It is known that a nearly optimal number of O(d log(n/d)) pools in two stages (where tests within a stage are done in parallel) are sufficient, but then the searcher must know d in advance. Here we explore group testing strategies that use a nearly optimal number of pools and a few stages although d is not known beforehand. We prove a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 28 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Alternatively, it is possible to dynamically adapt pooling sizes, when the measured rate of positive samples is different than expected. Finally, there exist some group testing algorithms [15,25] for the purpose of estimating the number of positive samples while using a relatively small (logarithmic) amount of tests, and such algorithms may be adapted to clinical constraints and parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible to dynamically adapt pooling sizes, when the measured rate of positive samples is different than expected. Finally, there exist some group testing algorithms [15,25] for the purpose of estimating the number of positive samples while using a relatively small (logarithmic) amount of tests, and such algorithms may be adapted to clinical constraints and parameters.…”
Section: Discussionmentioning
confidence: 99%
“…for an integer s. The following result [55,Theorem 4.3] shows that (5.6) satisfies certain success criteria.…”
Section: Nonadaptive Testingmentioning
confidence: 99%
“…Constructions based on (5.2) for a particular p( ) will struggle to distinguish between putative values k 1 and k 2 that are both far from . To overcome this, Damaschke and Muhammad [55,Section 4] proposed a geometric construction, dividing the range of tests into subintervals of exponentially increasing size and using a series of p( ) values tailored to each subinterval.…”
Section: Nonadaptive Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Damaschke [11] showed that Ω(log n) queries are needed for population size n using randomized non-adaptive group tests, to estimate within a constant factor c with a prescribed probability of underestimating d. Damaschke [10] proposes a Las Vegas strategy that uses O(d log n) pools in 3 stages and succeeds with any prescribed constant probability, arbitrarily close to 1.…”
Section: Group Testing Designsmentioning
confidence: 99%